Metastatic squamous cell carcinoma of unknown primary: a case report and brief literature review - Yang, Ying; Sun, Wei; Jia, Jun; Yu, Jing; Sun, Zhiwei; Du, Feng; Shi, Youwu; Sun, Jing; Gao, Songlin; Xiao, Yanjie; Zhang, Xiaodong (Frontiers in Oncology, 2025)
Carcinoma of unknown primary (CUP) is a rare malignancy characterized by metastatic disease without an identifiable primary tumor, even after extensive diagnostic evaluation. This case report described a 70-year-old female patient with squamous cell CUP (SCCUP) who initially presented with elevated carbohydrate antigen 19–9 and a diaphragmatic mass. Despite comprehensive workup, including 18F-fluorodeoxyglucose positron emission tomography–computed tomography and a 90-gene expression assay, the primary site remained unclear. The patient underwent surgical resection followed by two cycles of systematic therapy and achieved a disease-free survival of 14 months. This case underscores the limitations of the current diagnostic tools and the potential role of multimodal therapy in the management of CUP. The discordance between molecular testing and the clinical findings further emphasizes the perplexing nature of CUP. This report also reviews the literature on diagnosis and therapeutic options. Due to the absence of standardized regimens, future international collaboration and comprehensive genomic profiling are warranted to advance the understanding of this heterogeneous disease.